2021
DOI: 10.3389/fpls.2021.705446
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Zingiber Species Based on Analysis of Metabolite Profiles

Abstract: Zingiber corallinum and Zingiber montanum, which belong to the Zingiberaceae family, are traditional Chinese folk medicinal herbs in Guizhou and Yunnan Province of China. They share great similarities in morphology, chemical constituent, and DNA barcoding sequence. The taxonomy of the two Zingiber species is controversial and discrimination of traditional Chinese medicines directly affects the pharmacological and clinical effects. In the present study, we performed a systemic analysis of “super-barcode” and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 58 publications
4
11
0
Order By: Relevance
“…As demonstrated in previous research studies 6 , 27 , 28 , 71 , 72 , a large amount of cryptic biodiversity concealed amidst natural medical materials has not been discovered yet. DNA barcoding provided an effective tool for the discovery of cryptic species in the field of ecology and taxonomy 73 , 74 .…”
Section: Discussionmentioning
confidence: 92%
“…As demonstrated in previous research studies 6 , 27 , 28 , 71 , 72 , a large amount of cryptic biodiversity concealed amidst natural medical materials has not been discovered yet. DNA barcoding provided an effective tool for the discovery of cryptic species in the field of ecology and taxonomy 73 , 74 .…”
Section: Discussionmentioning
confidence: 92%
“…It is considered as the most valuable genomic resource for phylogenomics, species authentication and evolutionary studies due to its high copy number, potential for cross‐species amplification, uniparental inheritance, haploid nature, lack of recombination, low nucleotide substitution rate and availability of single copy genes (Hu et al 2017, Xue et al 2019, Daniell et al 2021). Phyletic patterns derived using Cp genomes has provided insights into crucial evolutionary events like colonization and speciation across all lineages of plants (Wu et al 2012), facilitated taxonomic revisions (Daniell et al 2021), supported genetic diversity (Magdy et al 2019, Li et al 2020a) and varietal discrimination studies (Li et al 2020b, Wang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that there is a complex biological composition in wild Chinese medicines [ 26 , 27 ]. Previous research has indicated misidentifications due to the great variety of Mantis Ootheca available which are morphologically similar [ 5 ].…”
Section: Discussionmentioning
confidence: 99%